ANALISIS HARGA SAHAM SYARIAH INDONESIA JAKARTA ISLAMIC INDEX MASA SEBELUM DAN SAAT COVID 19 - Nuryani, Anik; Marwanto, Ontot; Ratnawati, Tri (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACTThis study aims to test and analyze the Indonesian Jakarta Islamic Index's Islamic stock price which is influenced by 4 macroeconomic fundamentals (inflation, exchange rate / IDR, interest rates, stock trading volume) and shares of Indonesia's 5 largest trading partners (Shanghai Composite Index China shares, stocks Japanese Nikkei 225 Index, Singapore Straits Time Index shares, United States Dow Jones Industrial Average shares, India S&P BSE Sensex shares) before and during covid-19. The population in this study were Indonesian Islamic stocks listed on the IDX with the period March 2019 to September 2020. The sampling technique used a purposive sampling method and obtained one sample of the Jakarta Islamic Index (JII) stock index. The analytical method used is multiple linear regression analysis with SPSS application tools. Based on testing using the Simultaneous Model Test (Test F), it is known that the independent variables together (simultaneously) have a significant effect on the Sharia Indonesia Jakarta Islamic Index stock price before and during the Covid-19 period. While the results of the Hypothesis Test (t test) show that, the exchange rate of / Rp., China's Shanghai Composite Index (SCI) and the United States Dow Jones Industrial Average (DJIA) Stock Index have a significant effect on Islamic stocks in Indonesia Jakarta Islamic Index during covid-19. .